Phytochemical studies and biological evaluation of Artocarpus odoratissimus and Artocarpus sarawakensis, and some synthesis of pinostrobin pinocembrin derivatives / Nyotia Nyokat - Nyokat, Nyotia (2019)
Phytochemical study and biological evaluation were conducted on stem bark and roots of A. odoratissimus, and stem bark and leaves of A. sarawakensis. Previous studies revealed that Artocarpus species possess various biological activities such as cytotoxicity, antioxidant, antibacterial and anti-inflammatory. However, there are very few reports on the Artocarpus species from Sarawak. Besides, A. odoratissimus has not been studied intensively, and A. sarawakensis has not been reported before. Thus, this study aimed to develop a chemical profile of these species as well as to explorethe potential of both plants against microbial and other bioassays. Variouschromatographic methods such as vacuum liquid chromatography, column chromatography, and radial chromatography were used to isolate and purify compounds from the extracts of both plants. Structural elucidation was accomplished using spectroscopic methods such as ultraviolet, infrared, mass spectroscopy, ID nuclear magnetic resonance, and comparison with reported authentic data. The phytochemical study resulted in the isolation of two flavonoids; pinocembrin and pinostrobin, together with ten triterpenoids. Six compounds were isolated from A. odoratissimus. Taraxsteryl acetate and hexyl laurate were found in the stem bark, while, pinocembrin, pinostrobin, a-amyrin acetate, and P-amyrin acetate were isolated from the root extract. All compounds except taraxsteryl acetate were identified for the first time from A. odoratissiumus. Nine compounds were isolated from A. sarawakensis. a-Amyrin, B-amyrin, stigmasterol, a-amyrin acetate, J3-amyrin acetate, and hexyl laurate were isolated from the stem bark, while, y^^-sitosterol, lupeol, friedelin and stigmasterol were isolated from the leaves extract. Two flavonoids, namely pinostrobin and pinocembrin were synthesized and derived. The extracts for both species and some of the isolated pure compounds were tested for its antioxidant and antimicrobial activities. The^ antioxidant properties showed that the leaves methanolic extract of A. sarawakensis demonstrated the strongest free radical scavenging activity with IC50 value of 17.0 ug/mL and contained the highest phenolic content (2695.5 mg GAE/g). As for synthesized compounds, 3'-nitro-2-hydroxy-4, 6- dimethoxychalcone showed the highest antioxidant activity with IC50 value of 132.4 ug/mL. The microbial activity was carried out by disc diffusion and microdilution method for determination of the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). The stem bark methanolic extract of A. odoratissimus displayed very good activities towards S. pyogenes with MBC values 28.13 ug/mL and towards P. aeruginosa and E. coli 56.25 u^/mL followed by the stem bark ethyl acetate extract of A. odoratissimus towards S. pyogenes with MBC values of 56.25 ug/mL. All the synthesized compounds showed strong activity towards S. pyogenes and P. mirabilis with MIC values less than 100 ug/ mL. In the Lipoxygenase assay, the result showed a high inhibition of enzyme activity with 100.00 % inhibition for the stem bark and root ethyl acetate extracts of A. odoratissimus. Meanwhile, A. sarawakensis extracts revealed a moderate enzyme activity with 67.09 3.85 % and 64.19 2.37 inhibition for the leaves and stem bark ethyl acetate extracts. A total of 21 synthesized compounds were evaluated for the anticancer activity against the human breast cancer (MCF-7). Chalcones derivatives were found to have stronger activity than derivatives of pinostrobin and pinocembrin. Compound 2-hydroxy-4,6-dimethoxychalcone showed the most potent activity against MCF-7 with the percentage of inhibition value of 11.96 %.